Actitudes Que Tienen Cuatro (4) Adolescentes Hombres y Mujeres De Bogotá Hacia La Educación Sexual Recibida en Los Contextos Familiar y Escolar (2015)
The objective of this research is to describe the attitudes that four male and female adolescents from Bogotá towards the sexual education received in the contexts family and school; identifying the beliefs and knowledge internalized by the participants about sexuality in its dimensions: Communicative - relational, reproductive, erotic and affective, as well as the associated risk and protection behaviors to the cognitive and affective elements of the attitude reported by the participants. for this A semi-structured interview was carried out with two women and two men with ages between 13 and 17 years of age. The results show the interest of adolescents to deepen their knowledge about contraceptive methods, as well as perception of adults not belonging to their family nucleus, as distant, elusive and authoritarian; as well as the need of the adolescents interviewed for the expansion of the times stipulated in the sexuality education programs and their themes.